COMPARATIVE STUDY ON OUTCOME OF OPEN FISTULECTOMY VERSUS LIFT PROCEDURE FOR UNCOMPLICATED PERIANAL FISTULAS - HASSAN, HK; HUSSAIN, S; SHABBIR, A; AKHTAR, N; RASHEED, U; ULLAHA, S (Biological and Clinical Sciences Research Journal, 2024)
Perianal fistulas, particularly trans sphincteric types, pose a significant challenge in terms of management, often requiring surgical intervention. Traditional open fistulotomy has been a common procedure, but newer techniques like the ligation of the intersphincteric fistula tract (LIFT) procedure are being explored for improved outcomes, particularly in terms of preserving continence. This study aims to compare the outcomes of open fistulotomy versus the LIFT procedure in patients with trans sphincteric perianal fistulas. Objective: To compare the clinical outcomes, healing times, recurrence rates, and continence status between patients undergoing open fistulotomy and those treated with the LIFT procedure for trans sphincteric perianal fistulas. Methods: A prospective comparative study was conducted in the General Surgery Department of Nishtar Medical Hospital, Multan, from May 2024 to August 2024. A total of 150 adult patients with trans sphincteric perianal fistulas were enrolled using consecutive sampling. The patients were randomly divided into two groups: Group A (n = 75) underwent the LIFT procedure, and Group B (n = 75) underwent fistulectomy. Postoperative follow-up was conducted weekly until wound healing and at three months after healing to assess pain scores, recurrence rates, healing time, and continence status. Statistical analysis was conducted using SPSS Version 25, with a significance level set at p < 0.05. Results: Among the participants, 6 patients (8%) in Group A and 8 patients (10.7%) in Group B experienced recurrent fistulas, showing no significant difference between the groups. Postoperative pain scores were similar between both groups. However, the healing time was significantly shorter in Group A (27.2 days) compared to Group B (48.1 days) (p < 0.05). Recurrence rates were higher in Group A (16%) compared to Group B (2.7%) (p < 0.05). Incontinence was observed in 10.7% of patients in Group B, while no incontinence was reported in Group A (p < 0.05). Conclusion: The LIFT procedure offers better outcomes in terms of continence preservation and shorter healing time compared to open fistulotomy in the management of trans sphincteric perianal fistulas. However, open fistulotomy showed lower recurrence rates. These findings suggest that the LIFT procedure may be preferable in patients for whom preserving continence is a priority, while open fistulotomy may be a better option in cases where recurrence prevention is the main concern.